PENYULUHAN EEFEKTIVITAS TERAPI MUROTAL AL-QUR'AN TERHADAP TINGKAT KECEMASAN PADA IBU HAMIL TRIMESTER III - Siskha Maya Herlina; Yadul Ulya; Regina Pricilia Yunika (Jurnal Pengabdian Masyarakat DEDIKASI, 2023)
The anxiety experienced by mothers during pregnancy means that mothers tend to choose the easiest and fastest way to relieve anxiety. More and more women want to give birth with a labor process that takes place without pain and causes anxiety. Various methods are being used to reduce pain and anxiety during childbirth, both with pharmacological and non-pharmacological techniques.. Methods Non-pharmacological methods can also increase satisfaction during labor because the patient can control his feelings and strength. Objective: Relaxation, breathing techniques, movement and position changes, massage, hydrotherapy, hot/cold therapy, music (Murottal), guided imagery, acupressure, aromatherapy are several non-pharmacological techniques that can increase patient comfort during labor and have an effective influence on the birth experience. Results: Murotal therapy can speed up healing, this has been proven by various experts.The Effect of Murottal on Anxiety Listening to the Al-Qur'an has benefits in healing diseases, benefits from harmony in repetition of words and letters, benefits from balanced rhythm to the verses of the Koran, the impact of information in each verse, and beautiful harmonization Keywords: Murottal Al-Qur'an, Anxiety and Pregnant Women, Third Trimester